‘Zulu’ wooden vessels: the archive and the history of a genre - Nettleton, Anitra (Southern African Humanities, 2018)
In this paper I consider a particular genre of elaborately carved wooden vessels made in Natal between 1840 and 1900 against an archive located in both material objects, published images and published written texts. In unravelling the history of this genre, I consider the ways in which isiZulu-speakers used wooden receptacles and their production of objects for sale to outsiders. Unpacking both the ‘indigenous’ names given to these vessels, and to the only recorded individual artist, enables an understanding of the status of these objects within a larger corpus of artefacts categorise as ‘Zulu’ on one hand, and of objects made by traditional artists for outside patrons on the other. In the process it throws light on the ways in which the archive itself creates conditions for establishing differential categories of authenticity.